An Assessment of Knowledge level of Sugarcane farmers about Drip Irrigation System - Swetha. M , Sudha Rani. V and Sreenivasa Rao. I, (Indian Journal of Extension Education, 2018)
This research paper tries to find out the knowledge level of sugarcane farmers about drip irrigation system and also the profile characteristics influencing knowledge level of sugarcane drip farmers. The present investigation was carried out in three districts of Telangana state with 240 sugarcane drip farmers. The three districts were selected purposively as they had highest area under sugarcane cultivation. The results revealed that most of the sugarcane drip farmers had medium level of knowledge about drip irrigation system. Finally correlation and step-down regression analysis was used to find out the most influencing profile characteristics on level of knowledge of sugarcane drip farmers.